2019
DOI: 10.1007/s12221-019-8735-0
|View full text |Cite
|
Sign up to set email alerts
|

Blood-compatible Polyaniline Coated Electrospun Polyurethane Fiber Scaffolds for Enhanced Adhesion and Proliferation of Human Umbilical Vein Endothelial Cells

Abstract: The endothelialization and anti-thrombotic abilities of tissue engineered vascular scaffolds are considered to be effective properties for improving the performance small-caliber vascular scaffolds. For this purpose, we designed and developed electrically conductive fibrous scaffolds based on polyaniline coated polyurethane (PANI-PU) electrospun fibers for vascular tissue engineering applications. The porosity of PANI-PU fibers was 75.27±2.04 %. The obtained PANI-PU fibers were characterized by SEM observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…As shown in SEM images (Figure ), NO nanoparticles deposited more easily on the surface of eNO‐HS rather than eNO‐LS, which means more reduction in water contact angle of HS one in the result of more PVP on the surface. Hydrophilicity is important for tissue engineering scaffolds because proper hydrophilicity has a crucial effect on cell adhesion and spreading . Meanwhile, as it is known, increasing surface hydrophilicity lead to the formation of less interaction between the surface and components of blood, which has this potency to increase blood compatibility .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in SEM images (Figure ), NO nanoparticles deposited more easily on the surface of eNO‐HS rather than eNO‐LS, which means more reduction in water contact angle of HS one in the result of more PVP on the surface. Hydrophilicity is important for tissue engineering scaffolds because proper hydrophilicity has a crucial effect on cell adhesion and spreading . Meanwhile, as it is known, increasing surface hydrophilicity lead to the formation of less interaction between the surface and components of blood, which has this potency to increase blood compatibility .…”
Section: Resultsmentioning
confidence: 99%
“…To address these challenges, finding alternatives to autologous vessels have attracted so much attention and the efforts have focused on developing vascular substitutes . Synthetic polymers such as polyethylene terephthalate (PET), polytetrafluoroethylene (PTFE), polyurethane (PU), poly( l ‐lactic acid) (PLLA), poly(lactic‐co‐glycolic acid) (PLGA), and polycaprolactone (PCL) have been utilized to introduce cardiovascular devices such as vascular graft, artificial heart, and heart valves for the matter of their biocompatibility and controlled mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Although the biological properties of PANI in its native or modified form have already been studied, and cytotoxicity [5], interaction with stem cells [17], or interaction with tissues have already been reported, another important parameter of biocompatibility, namely interaction with blood has only been the subject of a few studies. The effect of PANI itself on platelet adhesion, hemolysis and plasma recalcification time has been studied by Li et al [18]. Here, PANI-coated polyurethane (PU) fibers were tested.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have reported that HUVECs grown on random electrospun fibers display a wellspread polygonal morphology and irregular distribution, which should be guided by the densely packed and randomly oriented nanofibers [61][62][63]. Sun et al reported that HUVECs on electrospun cross-linked gelatin membranes formed spherical or spindle morphology with plenty of pseudopodia attached to the fibers [62].…”
Section: Formation and Orientation Of Tube-like Structuresmentioning
confidence: 99%